2018
DOI: 10.1002/mrm.27080
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐vendor harmonization of T2‐relaxation‐under‐spin‐tagging (TRUST) MRI for the assessment of cerebral venous oxygenation

Abstract: This work suggests that harmonized TRUST MRI can yield highly compatible Y measurements across different vendors. Magn Reson Med 80:1125-1131, 2018. © 2018 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 50 publications
5
35
1
Order By: Relevance
“…The TRUST MRI technique used in our study allowed us to measure venous oxygenation, and therefore OEF, within 1.2 minutes of MRI examination time without injection of any exogenous agent or blood sampling. The technique used in this study has previously been tested for reproducibility and revealed an intrasession coefficient of variation of 2.0% ± 0.3, an intersession coefficient of variation of 2.6% ± 0.4 (29), and an interscanner coefficient of variation of 3.3% ± 0.6 (30).…”
Section: Discussionmentioning
confidence: 99%
“…The TRUST MRI technique used in our study allowed us to measure venous oxygenation, and therefore OEF, within 1.2 minutes of MRI examination time without injection of any exogenous agent or blood sampling. The technique used in this study has previously been tested for reproducibility and revealed an intrasession coefficient of variation of 2.0% ± 0.3, an intersession coefficient of variation of 2.6% ± 0.4 (29), and an interscanner coefficient of variation of 3.3% ± 0.6 (30).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report on multi-vendor comparison of TRUST MRI has demonstrated that the performance of these two implementations is highly compatible. 44…”
Section: Methodsmentioning
confidence: 99%
“…13 Test-retest studies with subject repositioning showed that the OEF results are minimally dependent on the slice location. 12 Sequence parameters of FLAIR were: 3D acquisition, sagittal FOV = 240 × 240 × 165 mm 3 , voxel size = 1.1 × 1.1 × 1.1 mm 3 , TR = 4.8 sec, TI = 1.65 sec, TE = 276 msec, and total scan time = 4.2 minutes.…”
Section: Mri Experimentsmentioning
confidence: 99%
“…11 Advantages of the TRUST technique over 15 O PET are that it is radiation-free, rapid, noninvasive (without injecting any contrast agent), and scalable (can be used on any 3T MRI scanner without special hardware). 12,13 Our aim was to examine the relationship of OEF, as measured by MRI, to Alzheimer's pathology and vascular risk factors in a group of cognitively impaired patients with mixed Alzheimer's and vascular pathology.…”
mentioning
confidence: 99%